2001
DOI: 10.1073/pnas.171321498
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 mutations in colorectal cancer probably occur before chromosomal instability, but after divergence of the microsatellite instability pathway

Abstract: Loss of chromosome 18q21 is well documented in colorectal cancer, and it has been suggested that this loss targets the DCC, DPC4͞ SMAD4, and SMAD2 genes. Recently, the importance of SMAD4, a downstream regulator in the TGF-␤ signaling pathway, in colorectal cancer has been highlighted, although the frequency of SMAD4 mutations appears much lower than that of 18q21 loss. We set out to investigate allele loss, mutations, protein expression, and cytogenetics of chromosome 18 copy number in a collection of 44 colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
117
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 34 publications
10
117
1
2
Order By: Relevance
“…Using the same procedures and selection algorithm, we identified only four candidate genes in this comparison. This group included the MADH4 gene, which has previously been reported to be homozygously mutated in HT29 (Woodford-Richens et al, 2001). No mutations were found in the remaining three candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Using the same procedures and selection algorithm, we identified only four candidate genes in this comparison. This group included the MADH4 gene, which has previously been reported to be homozygously mutated in HT29 (Woodford-Richens et al, 2001). No mutations were found in the remaining three candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Suitable PCR primers were designed for Smad 4 to amplify the exon regions of both the functional domains along with the 3 0 and 5 0 intron regions that are important for splicing (Woodford-Richens et al, 2001). RT-PCR primers were designed to cover the important functional regions of Smad 2 and variations in the expression of Smads were analysed by SQRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the low expression of Smad 2 in all of the tissue samples (premalignant and SCC) observed by us in human cervical cancer, loss of expression of Smad 2 was reported in head and neck squamous cell carcinoma by immunohistochemical analysis (MuroCacho et al, 2001). Homozygous deletions of Smad 4 were reported in pancreatic cancer and a 9 bp deletion of Smad 2 was reported in a human lung cancer cell line (Uchida et al, 1996), but in other cancers and other Smads usually the mutations reported are point mutations (MacGrogan et al, 1997;Miyaki et al, 1999;Woodford-Richens et al, 2001).…”
Section: Absence Of Smad 4 Expression Is Due To Loss Of Transcriptionmentioning
confidence: 99%
“…A similar spectrum of K-ras mutations is also found in MAP patients (Lipton et al, 2003a). In another Mendelian bowel tumour syndrome, hereditary nonpolyposis colon cancer (HNPCC), the effects of DNA mismatch repair (MMR) deficiency can be detected somatically through the presence of microsatellite instability (MSI) and frameshift mutations in short repeats within genes such as BAX and TGFBR2 (Woodford-Richens et al, 2001). It follows that, should some of the remaining MCRA cases be caused by a defect in DNA repair or by some other form of hypermutation, the somatic mutation spectrum will reflect the underlying cause of genomic instability.…”
mentioning
confidence: 99%